The ruling class [videorecording (DVD)] - Medak, Peter; O'Toole, Peter, 1932-2013; Sim, Alastair, 1900-1976; Lowe, Arthur, 1915-1982; Andrews, Harry, 1911-1989; Browne, Coral, 1913-1991; Barnes, Peter, 1931-2004 (Criterion collection, 2001)
A member of the House of Lords dies in a shockingly silly way, leaving his estate to his son. Unfortunately, his son is insane: he thinks he is Jesus Christ. He is "cured" of that affliction, only to become Jack the Ripper incarnate, blood thirsty Tory who is therefore sane and eminently acceptable to the House of Lords. An irreverant look at Britain's class system that peers behind the closed doors of the aristocracy.